School-family relationships: Challenges of the Covid-19 pandemic and emergency remote teaching from the teacher’s perspective (Research, Society and Development, 2021)
This research investigated the challenges of the school-family relationships during the COVID-19 pandemic and emergency remote teaching through the teacher’s perspective. It was conducted an exploratory cross-sectional research and a qualitative approach, involving 106 primary education teachers from schools located in the State of Rio de Janeiro. The educators answered the family-school relationship scale —adapted and shortened for the current study— and also an open question related to the challenges of the school-family relationships in the pandemic. The results of the quali-quantitative analysis revealed that teachers recognize that a good relationship between school and family is beneficial for the development of students. However, they blame the families for the issues that students face at school, distrust the quality of parental support in monitoring their children's studies, and point out that students are not interested in educational activities. Due to the pandemic, teachers highlighted some systemic challenges such as dealing with families, communication processes, proximal relationships, social inequalities and injustices, and the risks to the socio-emotional health of these actors. In conclusion, it is suggested to stimulate the discussion regarding the professional training of teachers on positive mechanisms of school-family interactions, such as the active participation and cooperation of parents in the educational experiences of children and adolescents.